Effect of shading and nitrogen fertilization on nitrogen metabolism, essential oil content and antimicrobial activity of Achillea millefolium - Lima, Milene Conceição; da-Silva, Cristiane Jovelina; Mariot, Marcio Paim; Freitag, Rogério Antônio; Serpa, Rosana; Ribeiro, Gladis Aver; Amarante, Luciano do (Acta Scientiarum. Biological Sciences, 2020)
The Achillea millefolium L. is a perennial herb with important antibacterial, antifungal, anti-inflammatory, antitumoral, and antioxidant properties. This research aimed to investigate the effect of shading (75%; black net) and nitrogen fertilization (0, 75 and 150 kg urea ha-1) on the nitrogen metabolism, essential oil yield and antimicrobial activity of A. millefolium at vegetative- and reproductive-stage. The evaluated parameters varied depending on the organ and the phenological stage of the plant considered. Overall, our findings indicated that shading decreased nitrogen assimilation. Decreased activities of nitrate reductase and glutamine synthetase were observed on shaded plants during reproductive and vegetative stages, respectively. Nitrate and total amino acid levels increased in shaded plants at the vegetative stage. Regarding nitrogen supply, the improved nitrogen metabolism and essential oil yield values were accompanied by intermediate concentrations of urea (75 kg ha-1). Plants fertilized with 75 kg urea ha-1 produced the highest amino acids concentration (vegetative stage), ammonium concentration (vegetative stage) and essential oil yield (reproductive stage). Shading or nitrogen supply did not influence the microbial activity of A. millefolium essential oil. However, the essential oil of leaves and flowers were highly effective against fungi and bacteria, especially gram-positive bacteria. In conclusion, the current study showed that full light and 75 kg urea ha-1 enhanced the nitrogen metabolism of A. millefolium in both vegetative and reproductive stages.